A ballistics module as a part of the fire control system - Luković, Branka R.; Petrović, Veljko P.; Mrdak, Veselin L. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This article presents a ballistics module as a part of the fire control system of weapons for fire support (mortars, artillery weapons and rocket launchers). The software is "open" with the prominence of autonomy work. It can be modulated and adapted on the user demand. Moreover, it is independent of the hardware base. Introduction: The fire control system is based on a ballistic module (BM) which determines the firing data for each weapon tool in the battery. Ballistic calculations, for the given position of the target in relation to the position of tools in the given weather conditions, determine firing data (elevation, direction, timing and locating devices) so that the missile seems to cause the desired effect. This paper gives the basic information about the features the BM performs and the manner of their implementation in the fire control system without going into algorithmic solution procedures. Ballistic problem in the fire control system: Ballistic calculation is based on a trajectory calculation of all kinds of projectiles (current, time-fuze, illuminating, smoke, with conventional propulsion, rocket, with built-in gas generator, etc.). Instead of previous solutions, where a trajectory calculation of the fire control system was done by approximate methods, in this BM the trajectory calculation is made by the same model with the same data as for a weapon and ammunition in the process of creating a firing table. The data used in the fire control system are made simultaneously with the preparation of firing tables for a particular tool and associated ammunition,. A modified model of particle, standardized at the NATO level, is also used. Taking into account the meteorological situation, before the trajectory calculation is done, a relative position of the target in relation to the position of the tool should be determined. A selection or loading check is carried out (possibility of reaching a given target) as well as the point at which the fuse is activated. The initial elevation of the tools that is used for calculating the trajectory to the end point should also be determined. The calculation is repeated until the final point of the trajectory coincides with a specific point by a projectile. During the preparation phase of fire, after all input parameters have been defined, the calculation is activated by the appropriate command. As an output from the BM, the initial firing data for the battery are determined: - Type of projectile, type of fuse, angle, distance table, locating devices and timing device (or the flight time); - Information and data: ordinate trajectory, angle of fall, terminal velocity, probable error of range and probable error of deflection. The demands placed on the ballistic module: In order to perform the functions of fire, the BM should provide, in addition to determining the elements for target practice, the solution to the following tasks: - Check the possibility to fire; - Correction and transfer of fire; - Group shooting, and - Planned fire. Ballistic testing of module: All ballistic modules (ballistic model, ballistic data, ballistic module software and the hardware that they will be implemented on) should meet the established requirements. The ballistic testing of the module is done in several stages, using a ballistic computer (BC) simulation model, the entire artillery system simulation program and the computer embedded in the target system. The ballistic computer simulation model allows input of all projected input data and displaying all the results of calculations in a batch and interactive mode. The ballistic model and ballistic data are tested by comparing them with the verification data obtained from simulation programs or parts of programs used for creating firing tables. Conclusion: Modern combat conditions impose increasing the efficiency and effectiveness of artillery fire by increasing the speed of response and shooting accuracy. The approximate methods used in the first stage of artillery computers inevitably caused inaccuracy of such data as well as a number of corrections, which increased the time required for firing at goal. In accordance with international standards, a module for calculating firing elements in the fire control system must be implemented by the same trajectory model and with the same ballistic data for the weapon and ammunition as well as in the procedure for the preparation of firing tables. Technological advances in hardware implementation ensure the implementation of such software. From the above mentioned reasons, the realized ballistic BM module shows the following benefits of the fire control system: significant increase of the speed, accuracy and efficiency of artillery fire, reduction of the number of persons required to perform its functions and a higher technological level.